“THE WORLD’S COLDEST, NEWEST AND MOST REMOTE CAPITAL” – THE PERCEPTION OF ASTANA BY THE BRITISH AND AMERICAN QUALITY PRESS: A CORPUS-ASSISTED ANALYSIS - Bączkowska, Anna; Khokhlacheva, Yelena (Scripta Neophilologica Posnaniensia, 2019)
Nur-Sultan (until recently called Astana), is the capital of Kazakhstan, which in 1998 was moved from Alma-Ata to a small village located in the central part of the country in the middle of a vast Kazakh Steppe. The capital is mostly known for its severe climate, futuristic and technologically advanced architecture, as well as for organizing international political and economic events, resulting from the growing power of Kazakhstan in Central Asia. The aim of this paper is to: (1) find out whether, and if so to what extent, the word Astana spurs interest in two British and two American newspapers representing right-wing and left-wing political alignment; (2) check how Astana is evaluated by these newspapers (whether in negative, positive, or neutral terms); (3) observe whether there are any differences between the conservative and the liberal papers as well as between the British versus American press. The material was gleaned from a ca. 35 billion word timestamped press corpus. Four subcorpora (altogether ca. 650,000 words in size) were created based on articles retrieved from The Daily Telegraph, The Guardian, Chicago Tribune and The New York Times, published between 2014-2018. The results have shown that the predominant themes in both British and American press include the ultramodern architecture of Astana and political events (international summits) organized in the capital. The majority of comments have positive or neutral evaluation.